Related Factors of Coronary Artery Disease and Stroke in Diabetes Speciality Clinic in Phaisali Hospital Phaisali District Nakhon Sawan Province. - บุญยืน สุรัตน์ (Journal of Preventive Medicine Association of Thailand, 2018)
The number of people with diabetes has been steadily increasing. A lack of supervision in diabetic patients may result in cardiovascular disease such as coronary artery disease and stroke. Therefore, the study of factors related to coronary artery disease and stroke in people with diabetes is extremely important. The study design was a cross-sectional study. The survey was conducted in the diabetes specialty clinic in Phaisali hospital, Phaisali District, Nakhon Sawan province. The sample consisted of 385 patients who visited to Phaisali hospital during the period 2014-2016 were conducted from medical records and the HOSxP data of Phaisali hospital in the period January-June 2016. Data were expressed as frequency, percentage, mean, and standard deviation. comparision among groups were analysed by Chi-Square test, Fisher Exact test and odds ratio. The study found that 62.30 % of the study group were female, 38.70 % were 61-70 years of age and the average age was 67.36, while 68.00 % of the comparison group were female, 25.30 % were 61-70 years of age and the average age was 61.05. Related factors of coronary artery disease and stroke in this study were chronic kidney disease stage IV-V (OR 4.856, p<0.001), atrial fibrillation (OR 6.826, p<0.001), use of simvastatin (OR 2.174, p<0.001), use of aspirin (OR 2.237, p 0.005), non-regular attendance to follow-up visits (OR 3.565, p<0.001), fasting blood sugar >130 mg/dl (OR 1.708, p 0.010), HDL level <40 mg/dl (OR 1.026, p 0.005), age >60 years (OR 3.565, p<0.001), systolic blood pressure >140 mmHg (OR 3.537, p<0.001) and diastolic blood pressure >90 mmHg (OR 2.621, p 0.008). The present study has shown that the elderly diabetic patients are vulnerable to coronary artery disease and stroke. Regular attendance to follow-up visits is very important. This study emphasized the role of controlling blood pressure, fasting blood sugar, HDL level and preserving kidney function to prevent these macrovascular complications.